Conceptual multifunctional design, feasibility and requirements for structural power in aircraft cabins - Nguyen,S; Millereux,A; Pouyat,A; Greenhalgh,E; Shaffer,M; Kucernak,A; Linde,P (Journal of Aircraft: devoted to aeronautical science and technology, 2021)
This paper presents a theoretical investigation into the potential use of structural power composites in regional aircraft passenger cabins and the corresponding challenges to widespread use, including fire-resistance, long-term cycling performance, and cost. This study focusses on adapting sandwich floor panels with structural power composite face sheets, designed to power the in-flight entertainment system. Using a simple mechanical model to define the structural requirements, based on state-of-the-art laminated structural power composites, a series of electrochemical energy storage performance targets were calculated: a specific energy > 144 Wh/kg, a specific power > 0.29 kW/kg, an in-plane elastic modulus > 28 GPa and in-plane tensile and compressive strengths > 219 MPa. Significantly, the use of a distributed energy storage system offered a significant range of other mass and cost savings, associated with a simplified power system, and the use of ground-generated electrical energy. For an Airbus A220-100, the analysis predicted potential mass and volume savings of approximately 260 kg and 510 land annual reductions in CO2and NOx emissions of approximately 280 tonnes and 1.2 tonnes respectively. This extended design analysis of a specific component highlights both the far-reaching implications of implementing structural power materials and the potential extensive systemic benefits.